2016
DOI: 10.1002/jbmr.3036
|View full text |Cite
|
Sign up to set email alerts
|

Romosozumab Improves Bone Mass and Strength While Maintaining Bone Quality in Ovariectomized Cynomolgus Monkeys

Abstract: Romosozumab (Romo), a humanized sclerostin antibody, is a bone-forming agent under development for treatment of osteoporosis. To examine the effects of Romo on bone quality, mature cynomolgus monkeys (cynos) were treated 4 months post-ovariectomy (OVX) with vehicle, 3 mg/kg, or 30 mg/kg Romo for 12 months, or with 30 mg/kg Romo for 6 months followed by vehicle for 6 months (30/0). Serum bone formation markers were increased by Romo during the first 6 months, corresponding to increased cancellous, endocortical,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
48
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 29 publications
7
48
0
1
Order By: Relevance
“…With romosozumab, that benefit may result from the rapid and substantial bone mass accrual, achieving more robust bone mass and improved bone structure prior to transitioning to the follow‐on antiresorptive therapy. In support of this, as has been shown in preclinical studies, romosozumab administration for 12 months in ovariectomized cynomolgus monkeys increased cortical and trabecular bone mass and thickness, and improved bone strength . Improvements in cortical thickness and increases in estimated bone strength of both cortical and trabecular bone at the spine and hip using CT and finite element analysis have also been observed in patients with postmenopausal osteoporosis receiving romosozumab …”
Section: Discussionsupporting
confidence: 73%
“…With romosozumab, that benefit may result from the rapid and substantial bone mass accrual, achieving more robust bone mass and improved bone structure prior to transitioning to the follow‐on antiresorptive therapy. In support of this, as has been shown in preclinical studies, romosozumab administration for 12 months in ovariectomized cynomolgus monkeys increased cortical and trabecular bone mass and thickness, and improved bone strength . Improvements in cortical thickness and increases in estimated bone strength of both cortical and trabecular bone at the spine and hip using CT and finite element analysis have also been observed in patients with postmenopausal osteoporosis receiving romosozumab …”
Section: Discussionsupporting
confidence: 73%
“…In a quantitative computed tomography (QCT) analysis of a subset of these participants, the effect of romosozumab was assessed on vBMD and bone mineral content (BMC) at the lumbar spine and total hip, and romosozumab was found to significantly increase integral vBMD and BMC at both sites from baseline and compared with both placebo and teriparatide groups . These findings were consistent with preclinical studies that showed increased bone mass after sclerostin inhibition, which also was associated with increased bone strength . Because finite element analysis (FEA) can provide a noninvasive assessment of strength changes after treatment, we sought to evaluate how the changes in vBMD and BMC observed in this study influenced FEA‐estimated strength at the spine and hip.…”
Section: Introductionsupporting
confidence: 62%
“…Regardless of the conditions that animals were subjected to (HLS alone, OVX alone, or HLS + OVX), histomorphometry analyses indicate that 5 weeks of Scl‐Ab administration resulted in a rapid and remarkable increase in cortical bone width, which is thought to be associated with robust bone formation at both the periosteum and endosteum. Similar results have been reported in studies of the effect of romosozumab (Scl‐Ab) on bone mass and strength in OVX animals . Our study, however, is the first to report that Scl‐Ab is capable of preserving cortical bone strength and structure by significantly improving bone formation indices in both the periosteum and endosteum.…”
Section: Discussionsupporting
confidence: 89%